Spherical Microresonators: Particular type of ultra‐sensitive optical tool for various sensing applications. Issue 1 (16th December 2015) - Weigel, Thomas; Esen, Cemal; Ostendorf, Andreas
Abstract: This article commemorates the 75th birthday of Prof. Dr. techn. Gustav Schweiger and his achievements in this field. Spherical microparticles are characterized by their extraordinary resonance properties. This makes it a promising tool for high sensitive measurements. Furthermore, the dependency on different physical quantities together with the possibility of targeted functionalization enables the measurement of a high variety of parameters with just one technology.